2001
DOI: 10.1520/jfs14973j
|View full text |Cite
|
Sign up to set email alerts
|

Stature Estimation from Radiographically Determined Long Bone Length in a Spanish Population Sample

Abstract: The estimation of stature from of a variety of bones is an important aspect of forensic work. In order to obtain reliable results, it is important to have comparative data obtained from the same population group as the skeletal remains. However, lack of up to date information on the population groups of Southern Europe makes the estimation of stature from bones in this area subject to possible error. In this study, the stature of 104 healthy adults from Spain was measured, and an anteroposterior teleradiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 5 publications
5
48
3
2
Order By: Relevance
“…For example, different equations have been established for predicting stature from knee height in white and black populations (Chunlea and Guo, 1992), Japanese (Myers et al, 1994;Knous and Arisawa, 2002), Hispanics (Palloni and Guend, 2005) and Thai people (Cheng et al, 2001). As ulna length-height relationships have also been established in different populations in different ways, care should be taken about extrapolation from children (Valk, 1971;Cheng et al, 1998;Gauld et al, 2004;Smith, 2007) to adults (Elia M (chairman & editor), 2003;Agnihotri et al, 2009;Auyeung et al, 2009), and vice versa, between different ethnic groups, (Joshi et al, 1964;Elia M (chairman & editor), 2003;Gauld et al, 2004;Auyeung et al, 2009), between different measurement techniques (Munoz et al, 2001;Elia M (chairman & editor), 2003;Gauld et al, 2004;Zhou et al, 2007) and between healthy subjects and those with marked osteoporosis or scoliosis. In one study involving community dwelling older Chinese (65-98 years) attending an osteoporosis centre, predictions of height based on ulna length was found to be comparable to that obtained from fibula length.…”
Section: Discussionmentioning
confidence: 99%
“…For example, different equations have been established for predicting stature from knee height in white and black populations (Chunlea and Guo, 1992), Japanese (Myers et al, 1994;Knous and Arisawa, 2002), Hispanics (Palloni and Guend, 2005) and Thai people (Cheng et al, 2001). As ulna length-height relationships have also been established in different populations in different ways, care should be taken about extrapolation from children (Valk, 1971;Cheng et al, 1998;Gauld et al, 2004;Smith, 2007) to adults (Elia M (chairman & editor), 2003;Agnihotri et al, 2009;Auyeung et al, 2009), and vice versa, between different ethnic groups, (Joshi et al, 1964;Elia M (chairman & editor), 2003;Gauld et al, 2004;Auyeung et al, 2009), between different measurement techniques (Munoz et al, 2001;Elia M (chairman & editor), 2003;Gauld et al, 2004;Zhou et al, 2007) and between healthy subjects and those with marked osteoporosis or scoliosis. In one study involving community dwelling older Chinese (65-98 years) attending an osteoporosis centre, predictions of height based on ulna length was found to be comparable to that obtained from fibula length.…”
Section: Discussionmentioning
confidence: 99%
“…These segmental lengths have been used as alternative measures of stature in the elderly, individuals with disabilities, and children with cerebral palsy (65)(66)(67)(68). These measures are also used by forensic pathologists and anthropologists to estimate height from skeletal remains (69,70). The aging process does not affect the long bones in the leg and arm (71), whereas aging does affect the length of the spine due to dessication of the vertebral disks.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…Thus knowing these segment measurements, which are defined is very helpful for determining the humerus length. (3) In this study, the mean values of the total length of the humerus was identified as 283.36, ± 22.48 mm and 290.17, ± 18.67 mm on left and right humerus respectively. In comparison to the findings of this study, the total mean values of the total humerus length was 283.36, ± 22.48 mm and 290.17, ± 18.67 mm on the left and right respectively.…”
Section: Discussionmentioning
confidence: 61%